PENGABDIAN MASYARAKAT SOSIALISASI BAHAYA GADGET & STRATEGI MEDIASI ORANGTUA UNTUK MENGENDALIKAN PENGGUNAAN GADGET PADA ANAK GENERASI Z DI SD IT SEHATI BINA INSANI KARAWANG - Sarini, Sarini; Lismayanti, Desty; Desrianti, Cindy; Asih, Mutiara Puspita (LP2M STP Mataram, 2024)
Advances in information and communication technology have had a significant impact on children, including the use of gadgets. Although gadgets also provide benefits in terms of accessing information and communication, their misuse can cause several problems such as addiction to playing gadgets, sleep disturbances, decreased academic achievement in children, and the risk of mental disorders in children. Given the many negative impacts of gadget use, especially on internet media users, where elementary school students often use gadgets in various places. The use of gadgets must be done wisely, especially in elementary school children. In order to avoid its misuse which will result in becoming victims and targets of crimes committed by criminals. Community service activities for socializing the use of gadgets are mainly aimed at parents of elementary school students aged between 6 - 8 years. Some conditions suggest that the intake of good information about the use of gadgets and the use of social media needs to be massively promoted so that children are not exposed to the negative impact of social media devices. The purpose of this socialization is to provide education to parents about parental mediation strategies and digital literacy wisely to be applied so that the use of gadgets in children can be controlled and not excessive. The use of gadgets should be able to provide good benefits to increase knowledge and information in improving the competence and creativity of students. The implementation of this socialization was carried out to 1 partner, namely the guardians of grade 1 and 2 students at SD IT Sehati Bina Insani Karawang, with the presentation of material, discussion, sharing, assistance and evaluation of activities. The results of this socialization activity increased parents' understanding and skills in conducting parent mediation and their digital literacy